2014
DOI: 10.2298/pif1404249g
|View full text |Cite
|
Sign up to set email alerts
|

Pectobacterium carotovorum subsp. carotovorum - the causal agent of broccoli soft rot in Serbia

Abstract: Soft rot symptoms were observed on broccoli plants in several commercial fields in the western part of Serbia. Six strains of bacteria were isolated from diseased tissues and identified as Pectobacterium carotovorum subsp. carotovorum using conventional bacteriological and molecular methods. All strains were non-fluorescent, gram-negative, facultative anaerobes, oxidase-negative and catalase-positive, causing soft rot on potato and carrot slices and did not induce hypersensitive reaction on tobacco leaves. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…It has been widely reported that P. fluorescens and P. carotovorum are responsible for head soft rot in broccoli (Gašić et al, 2014). However, in the present work, S. liquefaciens , together with Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely reported that P. fluorescens and P. carotovorum are responsible for head soft rot in broccoli (Gašić et al, 2014). However, in the present work, S. liquefaciens , together with Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Different species of bacteria can infect the florets of broccoli and produce head soft rot. Soft rot is caused by pectolytic bacteria capable of producing pectic enzymes, such as Pectobacterium carotovorum (formerly Erwinia carotovora ; Gašić et al, 2014), Pseudomonas fluorescens , Pseudomonas marginalis , and Pseudomonas brassicae (Aremu & Babalola, 2015). More recently, Clostridium spp., Cytophaga spp., and Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…atrosepticumабо Dickeya spp. не утворюють кислоти з α-метил глюкозиду та мальтози, але утилізують лактозу і трегалозу, і не продукують індол або лецитиназу [24].…”
Section: морфологічні характеристики колоній вірулентних ізолятівunclassified
“…Therefore, the soft rot test on potatoes was employed to identify the pectolytic Pectobacterium , but Pseudomonas was also reported to possess the same activity (Krejzar et al, 2008). Therefore, 16S rDNA sequences have been widely used and served as a gold standard technique for identifying P. carotovorum (Gasic et al, 2013; Hu et al, 2008; Lee et al, 2014). In addition, nucleotide sequences of the pectate lyase gene ( pel ) were also employed for the taxonomic identification of P. carotovorum (Baghaee‐Ravari et al, 2011; Faquihi et al, 2015; Golkhandan et al, 2013; Nazerian et al, 2011; Terta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%